Usulan Penerapan Preventive Maintenance dengan Menentukan Interval Waktu Perawatan untuk Mereduksi Downtime pada Mesin Water Jet Loom - Astri Permata Sari; Hidayat, Nita P. A. (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. CV Jaya Lestari is a company engaged in the Grey fabric manufacturing industry. This research was conducted in the Production Division which carried out the process of winding yarn until the yarn was woven to become a finished product, namely Grey cloth. The operating machines consist of ilsin machines, todo machines and water jet loom machines. The Water Jet Loom machine is the machine that has the highest downtime, which is 161.88 hours. Downtime on the Water Jet Loom machine resulted in the company not being able to produce gray cloth. Maintenance time intervals are carried out for the three critical components of the Water Jet Loom machine, namely the cutter, leno and feeder. The calculation results show that 80% reliability results in a maintenance interval for the cutter component of 48 hours, the leno of 59 hours, and the feeder of 23 hours. With the resulting maintenance interval, the downtime of the cutter component can be reduced to 2.44 hours, the leno component to 7.15 hours and the feeder component to 17.77 hours. Abstrak. CV Jaya Lestari merupakan perusahaan yang bergerak di bidang industri pembuatan kain Grey. Penelitian ini dilakukan di Divisi Produksi yang melakukan proses penggulungan benang hingga benang ditenun untuk menjadi produk jadi yaitu kain Grey. Mesin yang beroperasi terdiri dari mesin ilsin , mesin todo dan mesin water jet loom. Mesin Water Jet Loom merupakan mesin yang memiliki downtime tertinggi, yaitu 161,88 jam. Downtime pada mesin Water Jet Loom mengakibatkan perusahaan tidak dapat memproduksi kain grey. Interval waktu perawatan dilakukan untuk ketiga komponen kritis mesin Water Jet Loom, yaitu cutter, leno dan feeder. Hasil perhitungan menunjukkan bahwa keandalan 80% menghasilkan interval pemeliharaan komponen cutter sebesar 48 jam, leno sebesar 59 jam, dan feeder sebesar 23 jam. Dengan interval pemeliharaan yang dihasilkan, downtime komponen cutter dapat direduksi menjadi 2,44 jam, komponen leno menjadi 7,15 jam dan komponen feeder menjadi 17,77 jam.